Graphite dendrites in cast iron and their fundamental role in the control of morphology to obtain aero-eutectic graphite - Roviglione, Alicia (2021)
This work analyzes the growth of graphite in the eutectic system of gray cast iron, focusing on laminar type A and undercooled type D morphology, and a modified morphology, such as vermicular or compact graphite. The objective of the study is to find an optimal graphite structure, from which a new class of lightweight materials results that has been called aero-eutectic graphite (AEG). The method to obtain AEG consists of dissolving the gray iron ferrous matrix by means of a chemical attack. From experiences of unidirectional solidification, it has been found that laminar graphite grows in a non-faceted way, coupled to austenite, while in vermicular the growth is through foliated dendrites. This characteristic allows vermicular graphite to have a higher specific intrinsic surface area. According to the Brunauer-Emmett-Teller (BET) analysis, the surface of the vermicular was 106.27 m2 g−1, while those corresponding to type A and D were 83.390 m2 g−1 and 89.670 m2 g−1, respectively. AEG with graphite type D was used as a cathode in Li-O2 batteries with satisfactory results, reaching more than 70 charge and discharge cycles, and 150 cycles at this time and still cycling, using Ru(bpy)3(ClO4)2 as redox mediator.